(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
The first record from Ukraine of an alien species Amaranthus viridis L. (city of Kerson) is reported (). The description of the species, its diagnostic characters, primary and secondary (synanthropic) distribution and main characteristics of the habitat are provided.